Is dry needling effective for low back pain?: A systematic review and PRISMA-compliant meta-analysis. Issue 26 (June 2018) - Hu, Han-Tong; Gao, Hong; Ma, Rui-Jie; Zhao, Xiao-Feng; Tian, Hong-Fang; Li, Lu
Abstract: Background: To evaluate the efficacy and safety of dry needling (DN) for treating low back pain (LBP). Methods: Nine databases were searched from inception to October 2017. Eligible randomized controlled trials (RCTs) involving DN for treating LBP were retrieved. Two reviewers independently screened the articles, extracted data, and evaluated the risk of bias among the included studies using the risk of bias assessment tool by Cochrane Collaboration. Results: Sixteen RCTs were included and the risk of bias assessment of them was "high" or "unclear" for most domains. Meta-analysis results suggested that DN was more effective than acupuncture in alleviating pain intensity and functional disability at postintervention, while its efficacy on pain and disability at follow-up was only equal to acupuncture. Besides, DN was superior to sham needling for alleviating pain intensity at postintervention/follow-up and functional disability at postintervention. Additionally, qualitative review revealed that DN combined with acupuncture had more significant effect on alleviating pain intensity at postintervention and achieved higher response rate than DN alone. However, compared with other treatments (laser, physical therapy, other combined treatments, etc.), it remained uncertain whether the efficacy of DN was superior or equal because the results of included studies were mixed. Conclusions: Compared with acupuncture and sham needling, DN is more effective for alleviating pain and disability at postintervention in LBP, while its effectiveness on pain and disability at follow-up was equal to acupuncture. Besides, it remains uncertain whether the efficacy of DN is superior to other treatments. Nevertheless, considering the overall "high" or "unclear" risk of bias of studies, all current evidence is not robust to draw a firm conclusion regarding the efficacy and safety of DN for LBP. Future RCTs with rigorous methodologies are required to confirm our findings. Details of ethics approval: No ethical approval was required for this systematic review and meta-analysis. Abstract : Supplemental Digital Content is available in the text